∠ B A C = ∠ A D C = ∠ A D B = 9 0 ∘ and A B = 2 4 , B D = 3 .
A C can be expressed as a b , where a and b are positive integers, and b is square-free.
Find ( a + b ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The famous Pythagorean Theorem tells us A B 2 + A C 2 = B C 2 .
So, we can say─
A B 2 + A C 2 = B C ⋅ B C
⟹ A B 2 + A C 2 = B C ⋅ B C
⟹ A B 2 + A C 2 = B C ⋅ ( B D + C D )
⟹ A B 2 + A C 2 = B C ⋅ B D + B C ⋅ C D
Now let's split-up the last equality. Do the following equalities hold? A B 2 = B C ⋅ B D A C 2 = B C ⋅ C D
Yes, they hold (when A D ⊥ B C ).
B D A B = A B B C , which proves A B 2 = B C ⋅ B D
Now, As A B 2 = B C ⋅ B D , we get B C = B D A B 2 = 3 2 4 2 = 1 9 2 .
So, A C = B C 2 − A B 2 = 1 9 2 2 − 2 4 2 = 3 6 2 8 8 = 2 6 ⋅ 3 4 ⋅ 7 = 2 3 ⋅ 3 2 7 = 7 2 7 = a b .
Therefore, a = 7 2 , b = 7 with a + b = 7 9 .
Problem Loading...
Note Loading...
Set Loading...
First we observe that △ A B C ∼ △ A B D because their angles are congruent. Then, we can find the following relationship:
A B B D = A C A D
To find the length of A D we use the Pythagorean Theorem:
B D 2 + A D 2 = A B 2
3 2 + A D 2 = 2 4 2
9 + A D 2 + 5 7 6
A D = 5 6 7 = 3 4 ⋅ 7 = 9 7
Now we can find the length of A C :
A B B D = A C A D
2 4 3 = A C 9 7
3 ⋅ A C = 2 4 ⋅ 9 7
A C = 7 2 7
Since this answer is in its reduced form and the problem asks for a + b from a value in the form a b , the answer you should input is 7 2 + 7 = 7 9